"Agora patrimonial, instituto tecnológico de conservación patrimonial" "Plan parcial equilibrium, San Gil, Santander" (2017)
Through this degree work is sought to give a different look to the theme Heritage, through the creation of an educational project that is striking Both in the urban, design, structural, and technological part to give New experiences of disclosure of the heritage through Innovative technologies and an architecture that corresponds to the Contemporary but related to some concepts of the past, Generating an integral project that allows the teaching of the management and Protection of the heritage developed in the municipality of San Gil, Of Santander, to help the region become a national leader in The theme of heritage protection.